Should HIV discordant couples have access to assisted reproductive technologies? - Spriggs, M. (Journal of medical ethics, 2003)
In this paper we identify and evaluate arguments for and against offering assisted reproductive technologies (ART), specifically IVF, to HIV discordant couples (male partner HIV positive, female partner HIV negative). The idea of offering ART to HIV discordant couples generates concerns about safety and public health and raises questions such as: what is an acceptable level of risk to offspring and should couples who want this assistance be subject to selection criteria; should they undergo scrutiny about their suitability as parents when those who are able to conceive naturally face no such scrutiny and people with other illnesses are given access to ART? We conclude that offering ART to HIV discordant couples is likely to produce more benefit than harm and violates no ethical principles. Nevertheless, a decision to deny treatment need not constitute unjustified discrimination.